Efeito da aplicação de biocarvão, cama de frango e formulado npk no estado nutricional de laranjeira em terra mulata - Moline, Ederlon Flávio da Veiga [UNESP]; Lavres Júnior, José; da Silva, Darcilene Pereira; Clement, Charles Rol; Falcão, Newton Paulo de Souza (My University, 2015)
Growing in orange on Terra Mulata has been submitted nutrient limitation requiring correction in agricultural areas. The application of biochar associated with another source of nutrients can be a viable alternative to increase the efficiency of fertilizers and reduce losses in the areas. The objective of this study was to evaluate the effect of biochar, poultry litter and NPK in the nutritional status of orange trees grown in an Oxisol with anthropogenic A horizon (Terra Mulata). The study was conducted in a rural property landfall in Manacapuru (AM) in a randomized block design with eight treatments using biochar, poultry litter and NPK (4-14-8) applied in isolation and associates. To review two samples were taken at different periods of sheets to determine the nutritional status. Fertilizers applied did not increase the efficiency in the availability of contents of N, P, Fe and Zn, being the latter below the range of suitable content. As for the K, compost chicken manure and their combinations increased their availability, and the highest levels of Mg were found in the control treatment.
Effect of biochar, poultry litter and npk on the nutritional status of orange on terra mulata
Keywords: Amazonian soils; Biochar; Citrus sinensis; Plant nutrition